Age-Related Changes in the Plasticity of Neural Networks Assessed by Transcranial Magnetic Stimulation With Electromyography: A Systematic Review and Meta-Analysis - Tang, Xiaorong; Huang, Peidong; Li, Yitong; Lan, Juanchao; Yang, Zhonghua; Xu, Mindong; Yi, Wei; Lu, Liming; Wang, Lin; Xu, Nenggui (Frontiers in Cellular Neuroscience, 2019)
Objective: The excitability of cerebral cortical cells, neural pathway, and neural networks, as well as their plasticity, are key to our exploration of age-related changes in brain structure and function. The combination of transcranial magnetic stimulation(TMS) with electromyography (EMG) can be applied to the primary motor cortex; it activates the underlying neural group and passes through the corticospinal pathway, which can be quantified using EMG. This meta-analysis aimed to analyze changes in cortical excitability and plasticity in healthy elderly individuals versus young individuals through TMS-EMG. Methods: The Cochrane Library, Medline, and EMBASE databases were searched to identify eligible trials published from database inception to June 3, 2019. The Cochrane Risk of Bias Tool and improved Jadad scale were used to assess the methodological quality. A meta-analysis of the comparative effects was conducted using the Review Manager 5.3 software and Stata 14.0 software. Results: The pooled results revealed that the resting motor threshold values in the elderly group were markedly higher than those reported in the young group (mean difference [MD]: −2.35; 95% confidence interval [CI]: −3.69–−1.02]; p<0.00001). The motor evoked potential amplitude significantly reduced in the elderly group versus the young group (MD: 0.18; 95% CI: 0.09–0.27; p<0.0001). Moreover, there was significantly longer motor evoked potential latency in the elderly group (MD: −1.07; 95% CI: −1.77–−0.37]; p =0.003). There was no significant difference observed in the active motor threshold between the elderly and young groups (MD: −1.52; 95% CI: −3.47–−0.42]; p =0.13). Meanwhile, only two studies reported the absence of adverse events. Conclusion: We found that the excitability of the cerebral cortex declined in elderly individuals versus young individuals. The findings of the present analysis should be considered with caution owing to the methodological limitations in the included trials. Additional high-quality studies are warranted to validate our findings.